Novel fetal and maternal sonographic findings in confirmed cases of Beckwith–Wiedemann syndrome. (2nd February 2015) - Kagan, Karl Oliver; Berg, Christoph; Dufke, Andreas; Geipel, Annegret; Hoopmann, Markus; Abele, Harald
Abstract Objective The objective of the study was to examine the prenatal anomalies in fetuses with Beckwith–Wiedemann syndrome (BWS). Methods The study included a retrospective assessment of 12 pregnancies that were seen at three tertiary referral centres (Universities of Tübingen, Bonn, and Cologne/Germany). The genetic mutation, the results of the second trimester ultrasound examination, and the outcome of the pregnancies are shown. Biometric data were transformed into z‐values. Results Median gestational age at the time of examination was 22.6 (range 19.0–29.7) weeks of gestation. In all cases, the head circumference (HC) and the femur length (FL) were within the normal range, but the HC‐FL ratio was above the 95th centile in 75% of the cases. An exomphalos, macroglossia, and visceromegaly were observed in 67%, 50%, and 83% of the cases, and in 58% and 83%, there were polyhydramnios and placentamegaly respectively. The fetal pancreas was identified in three quarters of the cases. A third of the women had large, overstimulation‐like ovaries, although each pregnancy was conceived naturally. In four cases, beta‐human chorionic gonadotropin (hCG) levels were measured and mean hCG levels were 498 106 IU/L. Discussion Besides exomphalos, BWS should be considered if there is macroglossia, a distinct growth pattern, pancreatic hyperplasia, placentamegaly, and substantially increased levels of beta‐hCG. © 2015 John Wiley & Sons, Ltd.